Elucidating the Synergistic Behavior of Orientation‐Controlled SnS Nanoplates and Carbon Layers for High‐Performance Lithium‐ and Sodium‐Ion Batteries. Issue 8 (26th December 2021) - Lee, Jeongyoub; Choi, Changhoon; Lee, Hyungsoo; Ma, Sunihl; Tan, Jeiwan; Jang, Gyumin; Shim, Sang Gi; Park, Young Sun; Yun, Juwon; Kim, Dong‐Wan; Moon, Jooho
Abstract: As the demand for higher energy density in portable electronics and electric vehicles has increased, novel electrode materials with high reversible capacity have received significant research attention for breakthrough into next‐generation lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs). Tin monosulfide is a particularly promising anode material for both LIBs and SIBs due to its exceptional electrochemical properties, thus several strategies based on nanoengineered SnS/carbon composites (NSCs) have been introduced to improve the electrical and ionic conductivity and to reduce the volume change that occurs during cycling. However, to fully exploit the outstanding properties of NSCs, the crystallographic orientation of anisotropic SnS should be optimized. Herein, vertically aligned SnS nanoplate arrays (VA‐SnS@C) with preferred (111) and (101) orientations covered by carbon layers are fabricated using a facile spin‐coating method followed by a simple glucose solution bath. The as‐fabricated (111)‐oriented VA‐SnS@C anode demonstrates better electrochemical performance than does the (040)‐oriented planar SnS (PL‐SnS@C) anode, illustrating the critical role of the crystallographic orientation in NSCs. The superior electrochemical performance of the VA‐SnS@C anode demonstrates that this facile approach harnesses the synergistic effects of orientation‐controlled SnS and versatile carbon layers, which is crucial to design high‐performance anodes for next‐generation LIBs and SIBs. Abstract : The synergistic effect of orientation‐controlled tin monosulfide nanoplates and carbon layers is investigated for a high‐performance anode in next‐generation lithium and sodium‐ion batteries. By controlling the preferred crystallographic orientation of the SnS nanoplates, the nanoplates exhibit a strong electronic interaction with the carbon layers, leading to enhanced electrochemical performance due to the improved electrical conductivity, ion diffusion, and structural stability.